OPTIMIZATION OF SOCIAL MEDIA CREATIVE VIDEO CONTENT PRODUCTION AS A PROMOTION TOOL FOR SEGUNUNG CARANGWULUNG TRADITIONAL VILLAGE, JOMBANG - Hajidah Fildzahun Nadhilah Kusnadi (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2022)
Carangwulung village located in Wonosalam sub-district, Jombang district has the potential of abundant natural resources from plantation products ranging from bananas, durian, salak, to coffee. The large number of products produced in the Segunung Traditional Village is an interesting addition for implementers to focus on increasing promotions and marketing activities that can be carried out independently by the Segunung Traditional Village. The facilities owned by the Segunung Traditional Village ranging from coffee plantations, coffee shops, and springs should be able to make economic potential and tourism education potential that can be offered and make Segunung Traditional Village into a village that has independence in terms of the creative economy. However, the potential possessed by this Traditional Village is still not a tourism product that is well packaged and attractive for tourists who visit in a sustainable manner. This is partly due to the fact that activities have not been documented, village products are not properly published and are not published in an interesting way. Dusun Segunung has several social media options, but partners feel that creative content ideas are very difficult to grow. Starting from how photos, videos of creative products and designs can be managed properly and produced sustainably. The method of implementing community service is in the form of consultation, socialization and assistance on digital marketing strategies, especially in the form of creative videos and social media management. The socialization and mentoring covered material and practice on videography and video editing techniques using simple technology, smartphones. Through this activity, partners are expected to be able to optimize social media in promoting the potential of their villages, events and business products in order to reach a wider market so that business development and progress can ultimately increase the income of the Segunung Traditional Village.